1998
DOI: 10.1523/jneurosci.18-21-08936.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Major Cell Populations of the Mouse Retina

Abstract: We report a quantitative analysis of the major populations of cells present in the retina of the C57 mouse. Rod and cone photoreceptors were counted using differential interference contrast microscopy in retinal whole mounts. Horizontal, bipolar, amacrine, and Mü ller cells were identified in serial section electron micrographs assembled into serial montages. Ganglion cells and displaced amacrine cells were counted by subtracting the number of axons in the optic nerve, learned from electron microscopy, from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

110
1,115
9
13

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,248 publications
(1,269 citation statements)
references
References 37 publications
110
1,115
9
13
Order By: Relevance
“…Since the largest clones observed here did not contain more cells than the clones obtained by retroviral vectors analysis (Turner et al, 1990), this result reinforced our conclusion that the arrays are actual clones that arise from a single cell. Most interestingly, when we compared the proportion of the different cell types generated in the clones with that of previously published retroviral lineage tracing studies (Turner et al, 1990), or with proportions of the different cell types observed in the entire retinal cell population (Turner et al, 1990;Jeon et al, 1998), we found a general similarity both in terms of proportion of cells in the clones (Fig. 7G and Table 1), and as a proportion of clones containing at least one of each cell type ( Fig.…”
Section: Developmental Dynamicssupporting
confidence: 53%
“…Since the largest clones observed here did not contain more cells than the clones obtained by retroviral vectors analysis (Turner et al, 1990), this result reinforced our conclusion that the arrays are actual clones that arise from a single cell. Most interestingly, when we compared the proportion of the different cell types generated in the clones with that of previously published retroviral lineage tracing studies (Turner et al, 1990), or with proportions of the different cell types observed in the entire retinal cell population (Turner et al, 1990;Jeon et al, 1998), we found a general similarity both in terms of proportion of cells in the clones (Fig. 7G and Table 1), and as a proportion of clones containing at least one of each cell type ( Fig.…”
Section: Developmental Dynamicssupporting
confidence: 53%
“…30,41 They represent an invaluable tool for the study of cone PCD, given the detection problems that can arise in studying dynamic events in cells that account for a mere 2.8% of total photoreceptors in the mouse retina. 28 In spite of the fact that previous studies in our group ruled out the involvement of caspases in several in vitro and in vivo models of photoreceptor degeneration, [42][43][44] (data not shown) and -12 were active during apoptosis of 661W cells. This conflicting data can readily be explained if one considers the differences between the models employed.…”
Section: Discussionmentioning
confidence: 70%
“…An additional obstacle for the detection of cone apoptosis in the developing mouse retina arises from the fact that cones comprise less than 3% of the total photoreceptor population. 28 Knockout mice have, therefore, been indispensable in discerning the possible pathways executed by photoreceptors. A recent study by Zeiss et al 29 employing caspase-3 knockout mice found that ablation of the later did not completely inhibit developmental apoptosis but resulted only in a temporary delay.…”
Section: Introductionmentioning
confidence: 99%
“…The changes observed in the nob2 RGC function predict alterations in the peripheral vision of CSNB2 patients since the mouse retina has been considered in many important respects to resemble the primate retina outside of the fovea (Jeon et al, 1998). Currently, little is known about more complex visual phenotypes of CSNB2 patients, but our results would predict a deficit in vision mediated by the ON-center pathway under light-adapted conditions.…”
Section: Ganglion Cell Response Properties In Nob2 Micementioning
confidence: 63%